The risk of transplant failure with HLA mismatch in first adult kidney allografts from deceased donors - Williams, Robert C.; Opelz, Gerhard; McGarvey, Chelsea J.; Weil, E. Jennifer; Chakkera, Harini A. (Transplantation, 2016)
Background - Since the beginning of the technology, there has been active debate about the role of human leucocyte antigen (HLA) matching in kidney allograft survival. Recent studies have reported diminishing importance of HLA matching, which have, in turn, been challenged by reports that suggest the continuing importance of these loci. Given the controversies, we examined the effect of HLA compatibility on kidney allograft survival by studying all first adult kidney transplants in the United States from a deceased donor. - Methods - Using the United Network for Organ Sharing data, we identified first deceased donor kidney transplants between October 1, 1987, and December 31, 2013. Recipients were classified by their number of HLA mismatches. Cox multivariate regression analyses adjusting for recipient and donor transplant characteristics were performed to determine the impact of HLA compatibility on kidney allograft survival. - Results - Study cohort included 189 141 first adult kidney alone transplants, with a total of 994 558 years of kidney allograft follow-up time. Analyses adjusted for recipient and donor characteristics demonstrated a 13% higher risk (hazard ratio, 1.13; 95% confidence interval, 1.06-1.21) with 1 mismatch and a 64% higher risk (hazard ratio, 1.64, 95% confidence interval, 1.56-1.73) with 6 mismatches. Dividing the mismatch categories into 27 ordered permutations, and testing their 57 within mismatch category differences, demonstrated that all but 1 were equal, independent of locus. - Conclusions - A significant linear relationship of hazard ratios was associated with HLA mismatch and affects allograft survival even during the recent periods of increasing success in renal transplantation.
Accepted 21 November 2015
Gesehen am 03.02.2021